Critical orientations for humanising health sciences education in South Africa - Pentecost, M; Gerber, B; Wainwright, M; Cousins, T (BMJ Publishing Group, 2018)
In this article, the authors make a case for the ’humanisation' and ’decolonisation' of health sciences curricula in South Africa, using integration as a guiding framework. Integration refers to an education that is built on a consolidated conceptual framework that includes and equally values the natural or biomedical sciences as well as the humanities, arts and social sciences, respecting that all of this knowledge has value for the practice of healthcare. An integrated curriculum goes beyond add-on or elective courses in the humanities and social sciences. It is a curriculum that includes previously marginalised sources of knowledge (challenging knowledge hierarchies and decolonising curricula); addresses an appropriate intellectual self-image in health sciences education (challenging the image of the health professional); promotes understanding of history and social context, centring issues of inclusion, access and social justice (cultivating a social ethic) and finally, focuses on care and relatedness as an essential aspect of clinical work (embedding relatedness in practice). The article offers a brief historical overview of challenges in health and health sciences education in South Africa since 1994, followed by a discussion of contemporary developments in critical health sciences pedagogies and the medical and health humanities in South Africa. It then draws on examples from South Africa to outline how these four critical orientations or competencies might be applied in practice, to educate health professionals that can meet the challenges of health and healthcare in contemporary South Africa.